Mitogen‐activated protein kinase‐activated protein kinase‐2 (MK2) and its role in cell survival, inflammatory signaling, and migration in promoting cancer. Issue 2 (24th September 2021) - Morgan, Deri; Berggren, Kiersten L.; Spiess, Colby D.; Smith, Hannah M.; Tejwani, Ajay; Weir, Scott J.; Lominska, Christopher E.; Thomas, Sufi M.; Gan, Gregory N.
Abstract: Cancer and the immune system share an intimate relationship. Chronic inflammation increases the risk of cancer occurrence and can also drive inflammatory mediators into the tumor microenvironment enhancing tumor growth and survival. The p38 MAPK pathway is activated both acutely and chronically by stress, inflammatory chemokines, chronic inflammatory conditions, and cancer. These properties have led to extensive efforts to find effective drugs targeting p38, which have been unsuccessful. The immediate downstream serine/threonine kinase and substrate of p38 MAPK, mitogen‐activated‐protein‐kinase‐activated‐protein‐kinase‐2 (MK2) protects cells against stressors by regulating the DNA damage response, transcription, protein and messenger RNA stability, and motility. The phosphorylation of downstream substrates by MK2 increases inflammatory cytokine production, drives an immune response, and contributes to wound healing. By binding directly to p38 MAPK, MK2 is responsible for the export of p38 MAPK from the nucleus which gives MK2 properties that make it unique among the large number of p38 MAPK substrates. Many of the substrates of both p38 MAPK and MK2 are separated between the cytosol and nucleus and interfering with MK2 and altering this intracellular translocation has implications for the actions of both p38 MAPK and MK2. The inhibition of MK2 has shown promise in combination with both chemotherapy and radiotherapy as a method for controlling cancer growth and metastasis in a variety of cancers. Whereas the current data are encouraging the field requires the development of selective and well tolerated drugs to target MK2 and a better understanding of its effects for effective clinical use.